Genius [videorecording (DVD)] - Kidman, Nicole, 1967-; Law, Jude, 1972-; Firth, Colin, 1960-; Pearce, Guy, 1967-; Linney, Laura; Berg, A. Scott (Andrew Scott) (Roadside Attractions LLC, 2016)
A stirring drama about the complex friendship and transformative professional relationship between book editor Maxwell Perkins (who discovered F. Scott Fitzgerald and Ernest Hemingway) and Thomas Wolfe.